Towards a new politics of migration - Anderson, B (Taylor and Francis, 2017)
This paper reconsiders Stephen Castle’s classic paper Why Migration Policies Fail. Beginning with the so-called ‘migration crisis’ of 2015 it considers the role of numbers is assessing success or failure. It argues that in the UK public debates about immigration changed with EU Enlargement in 2004, when the emphasis shifted from concerns about asylum to concerns about EU mobility. Concerns were exacerbated by the government’s failure to meet its promise to reduce net migration. This policy is hampered by the general problem of definition of ‘migrant’ and the gap between statistical measures and popular usage in which ‘migration’ signifies problematic mobility. In fact, concern about migration has become a placeholder for concerns about globalisation and democratic accountability. A new politics of migration must make connections between migrants and citizens, but also between migration and other global processes, particularly outsourcing and the exploitation of labour and resources in the global south.